Comparation of the analytical and experimental models of 304SS corrosion rate in 0.5 m H2SS4 with bee wax propolis extract - Suprapto, Wahyono (Array, 2018)
Corrosion in the reservoir and transport vessel often causes a leak that leads to disaster. Data prediction and experimental corrosion in storage technology is very important to prevent damage and reduce maintenance costs. Theoretically, steel tank corrosion by sulfuric acid working medium can be minimized with the formation of sediments oxide by oxidation-reduction reaction. Behavioral inhibition of bee wax propolis on the 304SS in 0.5 M sulfuric acid was carried by potentiodynamic polarization. Based on the polarization testing the corrosion rate of the 304SS in a solution of 0.5 M H2SO4 is at 0.349 g/m2d with the missing mass amounted 5.21 x10 -9 g/s. In experiments, the inhibitor causing less mass loss is equal to 2.28 x 10 -11 g/s. Mass lost without and with inhibitor in this study is also known by theoretical calculations. The mass losses can be used to determine the inhibition efficiency. The calculation of the efficiency theoretically and experimentally gives the same result.